WOMEN'S PERCEPTION OF FADING BENEFITS FROM BEAUTY PRIVILEGE STEREOTYPES: PERSEPSI PEREMPUAN TENTANG PUDARNYA KEUNTUNGAN DARI STEREOTIP BEAUTY PRIVILEGE - Salwa Nurbaiah; Yuliana Hanami (SOSIOEDUKASI, 2025)
The phenomenon of beauty privilege is closely related to the standardization of beauty in Indonesia, particularly within the context of the workplace. Stereotypes surrounding beauty privilege assume that individuals who meet conventional beauty standards or possess attractive appearances gain certain advantages, such as preferential treatment, ease in obtaining employment, or opportunities for promotion. However, current trends indicate a shift in perceptions regarding the benefits of beauty privilege. This study aims to explore working women’s perceptions of the evolving meaning of beauty privilege and its role in the workplace. A descriptive qualitative approach was employed, using convenience sampling. Data were collected through interviews with three female participants from diverse professional backgrounds. The findings reveal that while beauty privilege still exists in certain employment sectors, its advantages are gradually diminishing. There is now a growing emphasis on individual competencies in the workplace, accompanied by a growing awareness that physical appearance is no longer the primary determinant of professional success. One of the positive impacts of the fading influence of beauty privilege is the increased freedom to work without the pressure to conform to conventional beauty standards, as well as greater motivation to develop and optimize one’s abilities. Furthermore, the decline of beauty privilege stereotypes helps reduce social envy among employees. These findings also reinforce the argument that skills are becoming the key factor in the workplace, although physical appearance may still play a supporting role.